Pengaruh Karakteristik Pesan pada Media Sosial dalam Membentuk User Engagement - Anggi Aldila Safitri (UNIVERSITAS SARI MUTIARA INDONESIA, 2021)
The growth of the internet in Indonesia provides an alternative for people looking for entertainment. In this case, it has been surveyed by a trusted source wearesociat.com, which produces data that internet growth in Indonesia has increased from year to year, namely by 54.7% in 2018 and continues to grow to 56% in 2019 of the total population in Indonesia. This shows that internet growth in Indonesia has increased by 17.3% in the 2018-2019 period (Nofriansyah, 2020:20). If in the past they had entertainment such as watching videos or films via television or radio, now people can access entertainment through devices, computers or laptops. The new media in this case is online video viewing services, namely Netflix. With a subscription system, people can be more efficient, fast and in accordance with the desired entertainment. This service is still relatively new, so companies have to make approaches and marketing to find customers. One of the media used by Netflix Indonesia is the Instagram account netflixid. So that researchers will see the effect of message characteristics on social media in shaping user engagement. Researchers used a quantitative method of content analysis of content posted on the netflixid Instagram account. There are two variables in this study, namely the independent variable related to post content messages (X) and the dependent variable related to user engagement. Variable X has three sub variables, namely the goal, message orientation, and elements in the netfixid Instagram post content. In this research, the message characteristics that have significance and influence on Netflix user engagement in Indonesia are found in the message element indicators in post content on the netflixid Instagram account.